2014
DOI: 10.3892/mmr.2014.1899
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of aquaporin-1 aggravates hippocampal damage in mouse traumatic brain injury models

Abstract: 'Secondary insult' following primary traumatic brain injury (TBI), including ischemia and edema, may aggravate brain impairments and affect the outcomes. The hippocampus is particularly sensitive to ischemia or edema due to its selective vulnerability, as neural cells of the hippocampus may be more prone to abnormal function or cell death in response to ischemia and edema. Aquaporin‑1 (AQP‑1) was reported to be associated with cerebral edema; however, the expression and role of AQP‑1 in hippocampal edema follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 45 publications
1
13
0
Order By: Relevance
“…Specifically AQP-1 is permeable only to water and is considered to participate in brain water homeostasis [54]. In addition, AQP 1 has been reported that it is involved in edema formation and cell death in the hippocampus following brain injury [55]. Following our results, we suggest that DHA may reduce osmotic water permeability following cerebral ischemia by inhibiting the expression of AQP-1.…”
Section: Discussionsupporting
confidence: 82%
“…Specifically AQP-1 is permeable only to water and is considered to participate in brain water homeostasis [54]. In addition, AQP 1 has been reported that it is involved in edema formation and cell death in the hippocampus following brain injury [55]. Following our results, we suggest that DHA may reduce osmotic water permeability following cerebral ischemia by inhibiting the expression of AQP-1.…”
Section: Discussionsupporting
confidence: 82%
“…Aquaporins (AQPs) are the water channels that can transport water across cell membrane in many tissues 36 . Upregulation of Aquaporin 1 (AQP1) caused hippocampal cell edema and delayed cell death following traumatic brain injury 37 , showing that sometimes it protects against neuronal cell damage 38 . However, AQP1 protein overexpression was associated with vacuolization in the astroglial cytoplasm in CA1 astrocytes, which may cause cell apoptosis 39 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, AQP5 gene silencing inhibits the proliferation of endometrial glandular epithelial cells notably [18], suggesting that altered AQP5 expression plays a crucial role in tumor progression. Up-regulation of Aquaporin1 (AQP1) gene has been reported to promote the invasiveness of glioma cells [19, 20]. However, the role of AQP5 gene expression in glioma has not been studied.…”
Section: Introductionmentioning
confidence: 99%